2016
DOI: 10.18632/oncotarget.10251
|View full text |Cite
|
Sign up to set email alerts
|

MMP7 interacts with ARF in nucleus to potentiate tumor microenvironments for prostate cancer progression in vivo

Abstract: ARF couples with TP53 in a canonical signaling pathway to activate cellular senescence for tumor suppressive function under oncogenic insults. However, the mechanisms on aberrant elevation of ARF in cancers are still poorly understood. We previously showed that ARF (p14ARF in human and p19Arf in mouse) elevation correlates with PTEN loss and stabilizes SLUG to reduce cell adhesion in prostate cancer (PCa). Here we report that ARF is essential for MMP7 expression, E-Cadherin decrease and the anchorage loss to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 40 publications
(52 reference statements)
1
43
0
Order By: Relevance
“…MMP7 (Xie et al, 2016) and MMP9 (Erdogan et al, 2016) Slug and Snail genes are master regulator of EMT that contributes to PCa progression and metastasis (Jethwa et al, 2008;Jin et al, 2010).…”
Section: Iscus I Onmentioning
confidence: 99%
“…MMP7 (Xie et al, 2016) and MMP9 (Erdogan et al, 2016) Slug and Snail genes are master regulator of EMT that contributes to PCa progression and metastasis (Jethwa et al, 2008;Jin et al, 2010).…”
Section: Iscus I Onmentioning
confidence: 99%
“…However, we found that MMP-7 localizes in the nucleus of prostate cancer cells with pro-enzyme form. 16 These data suggest that MMPs may undergo differential modifications during nuclear translocation. In conclusion, NLS-mediated import may link MMP to Importin proteins 16 and ARF-mediated protein modification may link MMP to SUMOylation, as we, our collaborators and other labs reported.…”
Section: Mechanisms Of Nuclear Localization Of Mmpsmentioning
confidence: 89%
“…We and our collaborators found that MMP-7 nuclear translocation and stability requires ARF-mediated tumor microenvironment for cell migration by disruption of cell adhesions. 16 Co-overexpression of MMP-7 and ARF resulted in greater cell migration, whereas knockdown of MMP-7 decreased wound healing ability of cells in prostate cancer. 16 Thus nuclear MMPs may promote cell migration greater than extracellular MMPs.…”
Section: Nuclear Mmps In Cell Migrationmentioning
confidence: 95%
See 2 more Smart Citations